2015
DOI: 10.1109/tsm.2014.2373636
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior of Residual Defects in Low-Dose Arsenic- and Boron-Implanted Silicon After High-Temperature Rapid Thermal Annealing

Abstract: We investigated the thermal behavior of defects remaining in low-dose (<10 13 cm −2 ) arsenic-and boronimplanted Si after high-temperature (1100 • C) rapid thermal annealing (RTA). The defects remaining after RTA were characterized as vacancy-type defects, and confirmed to be created by nonequilibrium states that occur during the extremely rapid cooling step of the RTA sequence. They were gradually removed by applying additional furnace annealing (FA) (i.e., thermal equilibrium heating process) at 300-400 • C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Many large amorphous regions remain after RTA at 600 °C for 1 s, however, the number and size of amorphous regions further decrease after RTA for 6 s. Finally, disordered regions completely disappear after RTA for 10 s. In previous study, Sagara et al revealed the residual defect formation in arsenic and boron implanted substrate after high temperature RTA process by low-temperature cathodoluminescence. 24) However, we confirm that there are no residual damage or defects in the substrate surface after the subsequent RTA process on the TEM view.…”
Section: Experimental Methodssupporting
confidence: 66%
“…Many large amorphous regions remain after RTA at 600 °C for 1 s, however, the number and size of amorphous regions further decrease after RTA for 6 s. Finally, disordered regions completely disappear after RTA for 10 s. In previous study, Sagara et al revealed the residual defect formation in arsenic and boron implanted substrate after high temperature RTA process by low-temperature cathodoluminescence. 24) However, we confirm that there are no residual damage or defects in the substrate surface after the subsequent RTA process on the TEM view.…”
Section: Experimental Methodssupporting
confidence: 66%
“…[9][10][11] Recently, detailed thermal behavior of residual damage in low-dose arsenic (As) and boron (B) implanted Si, after high-temperature rapid thermal annealing (RTA), has been investigated using cathode luminescence (CL). [12][13][14] However, most of these characterization techniques require sample preparation and restrict sample size. A non-destructive (hopefully non-contact, as well) characterization technique, without special sample preparation and sample size limitation, is desired for in-line monitoring of potential process and/or equipment related problems.…”
mentioning
confidence: 99%
“…[12][13][14] The defects remaining after RTA were characterized to be vacancy-type defects created during extremely rapid (nonequilibrium) cooling steps of the RTA sequence. Additional thermal equilibrium (or isothermal) heating in a furnace-type system, even at 300∼400…”
mentioning
confidence: 99%